The acyl-CoA Synthetase, pudgy, Promotes Sleep and Is Required for the Homeostatic Response to Sleep Deprivation - Thimgan, Matthew S.; Kress, Natalie; Lisse, Josh; Fiebelman, Courtney; Hilderbrand, Thomas (Frontiers in Endocrinology, 2018)
The regulation of sleep and the response to sleep deprivation rely on multiple biochemical pathways. A critical connection is the link between sleep and metabolism. Metabolic changes can disrupt sleep, and conversely decreased sleep can alter the metabolic environment. There is building evidence that lipid metabolism, in particular, is a critical part of mounting the homeostatic response to sleep deprivation. We have evaluated an acyl-CoA synthetase, pudgy (pdgy), for its role in sleep and response to sleep deprivation. When pdgy transcript levels are decreased through transposable element disruption of the gene, mutant flies showed lower total sleep times and increased sleep fragmentation at night compared to genetic controls. Consistent with disrupted sleep, mutant flies had a decreased lifespan compared to controls. pdgy disrupted fatty acid handling as pdgy mutants showed increased sensitivity to starvation and exhibited lower fat stores. Moreover, the response to sleep deprivation is reduced when compared to a control flies. When we decreased the transcript levels for pdgy using RNAi, the response to sleep deprivation was decreased compared to background controls. In addition, when the pdgy transcription is rescued throughout the fly, the response to sleep deprivation is restored. These data demonstrate that the regulation and function of acyl-CoA synthetase plays a critical role in regulating sleep and the response to sleep deprivation. Endocrine and metabolic signals that alter transcript levels of pdgy impact sleep regulation or interfere with the homeostatic response to sleep deprivation.